Comparison of intra articular autologous platelet-rich plasma with steroids in osteoarthritis knee: Experience from a North Indian tertiary care center - M N Arjun; Vivek Vasdev; Kunal Kishore; Arun Hegde; Krishnan Shanmuganandan; Abhishek Kumar; Uday Bhanu Kovilapu; Roopa Shivashankar (Indian Journal of Rheumatology)
Background: Intra-articular (IA) platelet-rich plasma (PRP) is a promising treatment option for knee osteoarthritis (OA). It accelerates the process of healing, ligament repair, cartilage regeneration, and bone formation when given in supraphysiological doses. The aim of this study was to compare the efficacy of IA PRP versus IA methylprednisolone acetate (MPA) in patients with knee OA. Methods: Open labeled prospective observational study was conducted on 60 patients with Kellgren-Lawrence Grade 2 and 3 OA knee, who fulfilled the ACR classification criteria for knee OA. Thirty patients were given IA PRP (6 ml) and 30 received IA methyl prednisolone (80 mg) at baseline line, which was repeated at 12 weeks. The primary endpoint was an improvement in Western Ontario and McMaster Universities Index (WOMAC) and 100 mm Visual Analog Scale (VAS) pain at 24 weeks postinjections. Results: The mean change in VAS pain and total WOMAC score from baseline to 24 weeks was 32.9 ± 12.1, 31.8 ± 14.7 for PRP group, and 12.9 ± 5.9, 7.5 ± 5.5 for MPA group, which was statistically significant (P < 0.0001). Conclusions: Treatment with IA PRP showed sustained improvements in WOMAC and VAS scores compared to IA steroids. PRP is an effective treatment for functional status and pain in moderate knee osteoarthritis.